Dirâsatu ‘Ilmu al-Lughat al-Nafsiyat ‘An Iktisâbu al-Lugah wa ‘Uyûbu al-Nuṭqi: A Psycholinguistic Studies on Language Acquisition and Speech Disorders - Hida, Ni'matulhidayah; Rizkyana Wahyu Laras Pertiwi (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2025)
Interest in language has rapidly developed since the 1950s, when Chomsky criticized Skinner's mechanistic approach to language acquisition. Psycholinguistics, which emerged from this debate, studies how humans process language, both in their first and second languages. Understanding language acquisition and speech disorders is a crucial topic as a contribution to the development of therapy methods and teaching techniques that can help individuals overcome difficulties in language and speech, making this field highly significant in both psychology and linguistics. This research examines three main aspects of psycholinguistics: language acquisition, the relationship between language and thought, and speech pathology. Using a literature review, this study highlights how psycholinguistics provides important insights into understanding the factors that affect language acquisition and its implications for language disorders. The findings of this study show that a deep understanding of linguistic processes can help linguists detect language acquisition problems at an early stage and design more effective interventions in language education. The practical implications of this research are highly relevant to the development of language teaching methods and therapy for language disorders, which can enhance individuals' communication skills and support cognitive development لقد تطور الاهتمام باللغة بشكل سريع منذ 1950 سنة، عندما انتقد تشومسكي المنهج الميكانيكي لسكنر في اكتساب اللغة. علم النفسي اللغوي الذي نشأ من هذا النقاش يدرس كيفية معالجة الإنسان للغة، سواء في اللغة الأولى أو الثانية. فهم اكتساب اللغة واعيوب النطق هو موضوع مهم للغاية كإسهام في تطوير أساليب العلاج وتقنيات التدريس التي يمكن أن تساعد الأفراد في التغلب على صعوبات اللغة والنطق، مما يجعل هذا المجال ذا أهمية كبيرة في علوم النفس واللغة. هذه الدراسة تستعرض ثلاثة جوانب رئيسية من علم النفس اللغوي: اكتساب اللغة، علاقة اللغة بالعقل، وعلم أمراض النطق. باستخدام دراسة الأدبيات، تبرز هذه الدراسة كيف يقدم علم النفس اللغوي رؤى هامة لفهم العوامل التي تؤثر على اكتساب اللغة، وكذلك تداعياته على اضطرابات اللغة. تشير نتائج هذه الدراسة إلى أن الفهم العميق للعملية اللغوية يمكن أن يساعد خبراء اللغة في اكتشاف مشاكل اكتساب اللغة في وقت مبكر، وتصميم تدخلات أكثر فعالية في تعليم اللغة. إن التداعيات العملية لهذه الدراسة ذات صلة كبيرة بتطوير أساليب تدريس اللغة وعلاج اضطرابات اللغة، مما يمكن أن يحسن مهارات التواصل لدى الأفراد ويدعم تطورهم المعرفي. Minat terhadap bahasa berkembang pesat sejak tahun 1950-an, ketika Chomsky mengkritik pendekatan mekanistik Skinner terhadap pemerolehan bahasa. Psikolinguistik, yang muncul dari perdebatan ini, mempelajari bagaimana manusia memproses bahasa, baik dalam bahasa pertama maupun kedua. Memahami pemerolehan bahasa dan gangguan bicara merupakan topik krusial sebagai kontribusi terhadap pengembangan metode terapi dan teknik pengajaran yang dapat membantu individu mengatasi kesulitan dalam berbahasa dan berbicara, menjadikan bidang ini sangat penting dalam psikologi dan linguistik. Penelitian ini mengkaji tiga aspek utama dalam psikolinguistik: pemerolehan bahasa, hubungan antara bahasa dan pemikiran, serta patologi bicara. Dengan menggunakan metode tinjauan pustaka, penelitian ini menyoroti bagaimana psikolinguistik memberikan wawasan penting dalam memahami faktor-faktor yang memengaruhi pemerolehan bahasa serta implikasinya terhadap gangguan bahasa. Hasil penelitian ini menunjukkan bahwa pemahaman yang mendalam tentang proses linguistik dapat membantu linguis dalam mendeteksi masalah pemerolehan bahasa sejak dini serta merancang intervensi yang lebih efektif dalam pendidikan bahasa. Implikasi praktis dari penelitian ini sangat relevan bagi pengembangan metode pengajaran bahasa dan terapi untuk gangguan bahasa, yang dapat meningkatkan keterampilan komunikasi individu serta mendukung perkembangan kognitif.